2018
DOI: 10.12693/aphyspola.134.349
|View full text |Cite
|
Sign up to set email alerts
|

Dry Sliding Wear Behaviour of Shot Peened TI6AL4V Alloys at Different Peening Times

Abstract: Titanium alloys have been extensively used in biomedical and aerospace applications, where the fatigue life and tribological behaviour are important. Shot peening is a cold working mechanical surface treatment and has been widely used to improve specifically the fatigue life of titanium alloys for the last decades. In this study, the effect of shot peening on the dry sliding wear behaviour of Ti6Al4V alloy was investigated. Moreover, the influences of peening time on the surface topography and the dry sliding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The surface roughness significantly increased at the higher pressure since the crater formation resulted in an uneven surface (Figure 7b) [40]. Crater formation was the active deformation mechanism that modified the surface and changed the roughness via the formation of irregular valleys and peaks in the surface profile, similar to the results reported in the literature [4,25,55,56,63]. The influence of cover rate on the surface roughness was insignificant at the low pressure, whereas the [20], ECAP2 [77], HPT [31], ARB [17], CGP [71], HE [77], SP, homogenisation annealing.…”
Section: Surface and Subsurface Features Of Shot-peened Aa1050 Alloysupporting
confidence: 83%
See 1 more Smart Citation
“…The surface roughness significantly increased at the higher pressure since the crater formation resulted in an uneven surface (Figure 7b) [40]. Crater formation was the active deformation mechanism that modified the surface and changed the roughness via the formation of irregular valleys and peaks in the surface profile, similar to the results reported in the literature [4,25,55,56,63]. The influence of cover rate on the surface roughness was insignificant at the low pressure, whereas the [20], ECAP2 [77], HPT [31], ARB [17], CGP [71], HE [77], SP, homogenisation annealing.…”
Section: Surface and Subsurface Features Of Shot-peened Aa1050 Alloysupporting
confidence: 83%
“…SP was performed on the metallographically prepared AA1050 Al alloy samples with stainless-steel shots (diameter: 0.7-1.0 mm (type: Chronital S60), shot hardness: 450 HV) as detailed elsewhere [55,56]. Figure 1 shows the SP of AA1050 by highlighting some of the important parameters and dimensions.…”
Section: Shot Peening Processmentioning
confidence: 99%
“…Several surface treatments are employed to enhance the durability and longevity of titanium and its alloys. These techniques include heat treatment, shot peening [13], anodic plasma electrolytic oxidation [14], laser surface modification [15], and plasma-based ion implantation [16]. Additionally, the use of coatings such as diamond-like carbon films [17], PEO coatings [14], and graphene oxide [18] has been explored to enhance the wear resistance of Ti6Al4V alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, certain aspects remain to be clarified, including the mechanism of SP strengthening and the impact of SP parameters on the surface properties, wear resistance, fatigue resistance, and corrosion resistance of the workpiece. Avcu et al [19] proposed that shot peening significantly impacts the wear behavior of TI6AL4V alloy, yet they did not elucidate the mechanism by which shot peening enhances its wear resistance. Khun et al [20] found that increasing shot peening pressure enhanced the mechanical properties of SAE 1070 steel; however, they overlooked the potential influence of other shot peening parameters on its mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%